Bridging the biodiversity financing gap - Angelina Hackmann (Leibniz Institute for Financial Research SAFE, 2024)
In recent decades, biodiversity has declined significantly, threatening ecosystem services that are vital to society and the economy. Despite the growing recognition of biodiversity risks, the private sector response remains limited, leaving a significant financing gap. The paper therefore describes marketbased solutions to bridge the financing gap, which can follow a risk assessment approach and an impact-oriented perspective. Key obstacles to mobilising private capital for biodiversity conservation are related to pricing biodiversity due to its local dimension, the lack of standardized metrics for valuation and still insufficient data reporting by companies hindering informed investment decisions. Financing biodiversity projects poses another challenge, mainly due to a mismatch between investor needs and available projects, for example in terms of project timeframes and their additionality.
Keywords: 330; Biodiversity; Green Finance; Financing Gap